2011
DOI: 10.4314/ijbcs.v4i5.65580
|View full text |Cite
|
Sign up to set email alerts
|

Paramètres démographiques des cheptels de bovins Borgou et N’Dama à la Ferme d’Elevage de l’Okpara au nord-est du Bénin

Abstract: RESUME

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 11 publications
0
3
0
2
Order By: Relevance
“…The female zebu Azawak is considered the best dairy in West Africa (Issa et al 2014). The local breed Borgou is considered to be a fairly resistant animal to the harsh climatic conditions of its living environment (Youssao et al 2013a) and has a fairly good resistance to trypanosomiasis, which is endemic to Benin (Alkoiret et al, 2016). The product from the cross between the Azawak bull and the Borgou cow, will therefore bene t from the complementarity of the two breeds.…”
Section: Livestock Characteristicsmentioning
confidence: 99%
“…The female zebu Azawak is considered the best dairy in West Africa (Issa et al 2014). The local breed Borgou is considered to be a fairly resistant animal to the harsh climatic conditions of its living environment (Youssao et al 2013a) and has a fairly good resistance to trypanosomiasis, which is endemic to Benin (Alkoiret et al, 2016). The product from the cross between the Azawak bull and the Borgou cow, will therefore bene t from the complementarity of the two breeds.…”
Section: Livestock Characteristicsmentioning
confidence: 99%
“…The seasonal fluctuation of prices may due to the seasonal variation of fodder and feed resources in term of nutritional value and quantity for lactating cow in farms (Agossou et al, 2017). Indeed, evidence demonstrated that due to high nutritive value and abundance of feed during rainy season, lactating cow produce more milk than during drought season (Soule et al, 2017;Alkoiret et al, 2016). The processing costs averagely 49,300 FCFA per month.…”
Section: Business Management and Sustainable Competitiveness Of Dairymentioning
confidence: 99%
“…Ces troupeaux sont constitués entre 65 et 75 % de femelles (Dehoux et Hounsou-Vè, 1993 ;Alkoiret et al, 2010b). De même, dans la sous-région ouest africaine les vaches dominent les troupeaux (45 à 80 %) et sont généralement utilisées pour la production du lait dans les cheptels bovins du Sénégal (Ejlertsen et al, 2011), les troupeaux bovins des petits producteurs laitiers de Gambie (Somda et al, 2005) et les troupeaux bovins des Peuls agropasteurs du Nigeria (Daodu et al, 2009 ;Akpa et al, 2012).…”
Section: Analyses Statistiquesunclassified
“…Les bovins sont les principaux pourvoyeurs de viande et de lait des populations locales. Diverses études ont été réalisées pour caractériser les performances des bovins élevés en station dans des conditions semi-intensives (Alkoiret et al, 2010b ;Gbangboché et Alkoiret, 2011). Les différents paramètres collectés ne représentent qu'en partie la réalité des troupeaux bovins béninois.…”
Section: ■ Introductionunclassified